Evaluation of fermented African mesquite seed (Prosopis africana) on growth and nutrient digestibility of Nile tilapia (Oreochromis niloticus) fingerlings - Shina Al-Habeeb Aroyehun; Wilfred Olusegun Alegbeleye; Olubunmi Temilade Agbebi; Abiodun Akinde (Journal of Fisheries, 2021)
Production of cheap and quality dietary protein to replace the expensive conventional protein was studied in an 84-day feeding trial of Nile tilapia Oreochromis niloticus. African mesquite (Prosopis africana) seeds were subjected to fermentation processes and four iso-nitrogenous diets (35% crude protein) were formulated to contain graded levels of fermented African mesquite seed meal (FMS) to replace soybean meal (SBM) at four inclusion levels (0%, 15%, 30% and 45%) replicated in a completely randomised design. Proximate analysis showed increased in crude protein (35.10% to 41.29%), amino acids concentration, minerals content (calcium and phosphorus) while there were reductions in crude fibre (7.79% to 2.13%), crude lipids (4.02% to 2.67%) and anti-nutritional factors of FMS. The highest protein digestibility of 83.35% was recorded in FMS30 while FMS15 showed the least (77.07%). Carcass compositions were affected by diets composition. The minimum feeding cost of US$ 0.88 kg−1 was registered in FMS45 while FMS15 recorded the highest value of US$ 1.37 kg−1. In conclusion, 45% of FMS could replace SBM without compromising growth performance of Nile tilapia.